2020
DOI: 10.1080/13607863.2020.1725739
|View full text |Cite
|
Sign up to set email alerts
|

Discerning rural Appalachian stakeholder attitudes toward memory screening

Abstract: Objective:The aim of this descriptive study was to examine Appalachian stakeholder attitudes toward routine memory screening, and to compare and contrast results from a similar study conducted in an ethnically diverse rural Florida cohort. Determining perceptions about memory screening is essential prior to developing culturally relevant programs for increasing early dementia detection and management among rural underserved older adults at risk of cognitive impairment. Benefits of early detection include rulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
(64 reference statements)
0
15
0
1
Order By: Relevance
“…Researchers have previously shown that providing information regarding AD can increase AD knowledge in long-term care settings (Dassel et al, 2020) and in rural communities (Wiese et al, 2017(Wiese et al, , 2020a(Wiese et al, , 2020b(Wiese et al, , 2020c. Providing education regarding AD has been shown to increase racially/ethnically diverse faith-based participants in memory screenings (95%; Daccarett et al, 2021) and completed provider referrals (84-95%; Wiese et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have previously shown that providing information regarding AD can increase AD knowledge in long-term care settings (Dassel et al, 2020) and in rural communities (Wiese et al, 2017(Wiese et al, , 2020a(Wiese et al, , 2020b(Wiese et al, , 2020c. Providing education regarding AD has been shown to increase racially/ethnically diverse faith-based participants in memory screenings (95%; Daccarett et al, 2021) and completed provider referrals (84-95%; Wiese et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been tested in over 600 rural older adults, with a pre-post effect size of r = 0.81, indicating a large effect size (Lakens, 2013). However, tests for reliability and validity have been favorable, including Cronbach's alpha = .84 and overall Rasch item analysis of .94 (Wiese et al, 2017(Wiese et al, , 2020a(Wiese et al, , 2020b(Wiese et al, , 2020c(Wiese et al, , 2021.…”
Section: The Bkadmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rural residents not only may be more accustomed to self-isolation and cohesive family interdependence, but they may actively cultivate these lifestyle qualities. 48,49 Thus, sheltering in place may not feel as constricting as it would to an urban or suburban resident. We may be able to discern much from the rural community about how to effectively adjust and live so as to successfully weather this pandemic and minimize related adverse mental health sequelae.…”
mentioning
confidence: 99%
“…The reason that individuals in rural communities are at diminished risk is merely a matter of density: the same reason why state governors and local municipalities initially banned gatherings of over 50 people, subsequently reduced them to 10, and in some cases as few as 2. Furthermore, rural residents not only may be more accustomed to self‐isolation and cohesive family interdependence, but they may actively cultivate these lifestyle qualities 48,49 . Thus, sheltering in place may not feel as constricting as it would to an urban or suburban resident.…”
mentioning
confidence: 99%